Do Cory’s shearwaters Calonectris diomedea synchronize laying among close neighborhoods? A reappraisal using data from artificial nest sites - Catry, Paulo (2012)
Previous studies of Cory’s shearwater nesting biology suggest that pairs nesting at very close range to one another lay their eggs more synchronously than the colony as a whole. However, such apparent synchrony could be confounded by the existence of spatial structure in the quality of nesting sites and, hence, quality of the birds occupying the nests. If laying dates differ between sites of different quality, then synchrony is just a by-product of the spatial arrangement of nest sites. In this study, we show that when studying laying dates in artificial nests of uniform quality, no local synchronization of laying could be detected. We point to other shortcomings of previous analyses and conclude that, although Cory’s shearwaters show remarkably synchronized attendance behaviors at the nesting sites, there is no conclusive evidence showing that laying dates are influenced by the behavior of near neighbors.